Early visual training and environmental adaptation for infants with visual impairment. (4th May 2021) - Fazzi, Elisa; Micheletti, Serena; Calza, Stefano; Merabet, Lotfi; Rossi, Andrea; Galli, Jessica; ,
Abstract : Aim: To evaluate the effectiveness of early visual training and environmental adaptation on visual function and neurological development in infants with visual impairment. Method: This was a pilot intervention clinical trial study. Thirty infants (mean age 5.9mo, SD 2.1mo, range 4–11mo; 16 males, 14 females) with peripheral visual impairment (PVI, n =15) or cerebral visual impairment (CVI, n =15) participated in a 6‐month visual intervention programme. Thirty matched infants (mean age 6mo, SD 1.4mo, range 4–9mo; 18 males, 12 females) served as a comparison group. Primary outcome measures were visual acuity, contrast sensitivity, and qualitative ocular motor functions. Secondary outcomes were scores on the Griffiths Mental Developmental Scales (GMDS). Results: The treatment group showed a significant improvement in all the primary outcomes ( p <0.01). The comparison group improved only in visual acuity and contrast sensitivity ( p <0.01). The treatment group showed greater improvement than the comparison group in visual fixation ( p =0.033) and smooth pursuit ( p <0.01). The CVI subgroup showed greater improvement in visual acuity than the PVI subgroup ( p <0.01). GMDS subscales of hand–eye coordination ( p =0.01) and performance ( p <0.01) increased in the treatment group, while the total score of the comparison group decreased, driven by language ( p =0.039) and hand–eye coordination ( p =0.025) subscales. Interpretation: Results suggest that, in infants with visual impairment, visual function and certain developmental outcomes improve in response to early visual training and environmental adaptation, in an interactive context. What this paper adds Early visual training and environmental adaptation are associated with enhanced visual acuity and smooth pursuit. Early visual training and environmental adaptation are associated with an improvement of neurological developmental outcome. Performance, hand–eye coordination, and language scores in Griffiths Mental Developmental Scales increase after visual training. After training, visual acuity improves more in infants with cerebral rather than anterior visual impairment. Type and complexity of visual impairment contribute to determine infants' response to training. What this paper adds: Early visual training and environmental adaptation are associated with enhanced visual acuity and smooth pursuit. Early visual training and environmental adaptation are associated with an improvement of neurological developmental outcome. Performance, hand–eye coordination, and language scores in Griffiths Mental Developmental Scales increase after visual training. After training, visual acuity improves more in infants with cerebral rather than anterior visual impairment. Type and complexity of visual impairment contribute to determine infants' response to training. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Entrenamiento visual temprano y adaptación ambiental para bebés con discapacidad visual: Objetivo: Evaluar la efectividad del entrenamiento visual temprano y la adaptación ambiental en la función visual y el desarrollo neurológico en bebés con discapacidad visual. Método: Este fue un estudio piloto de intervención clínica. Treinta lactantes (edad media 5, 9 meses, DE 2, 1 meses, rango de 4 a 11 meses; 16 varones, 14 mujeres) con discapacidad visual periférica (PVI, n = 15) o discapacidad visual cerebral (CVI, n = 15) participaron en un programa de intervención visual que duro 6 meses. Treinta lactantes emparejados (edad media 6 meses, DE 1, 4 meses, rango 4‐9 meses; 18 varones, 12 mujeres) sirvieron como grupo de comparación. Las medidas de resultado primarias fueron la agudeza visual, la sensibilidad al contraste y las funciones motoras oculares cualitativas. Los resultados secundarios fueron puntuaciones en las Escalas de desarrollo mental de Griffiths (GMDS). Resultados: El grupo de tratamiento mostró una mejora significativa en todos los resultados primarios (p <0, 01). El grupo de comparación mejoró solo en agudeza visual y sensibilidad al contraste (p <0.01). El grupo de tratamiento mostró una mayor mejora en la fijación visual (p = 0, 033) y la búsqueda suave (p <0, 01). El subgrupo CVI mostró una mayor mejora en la agudeza visual que el subgrupo PVI (p <0, 01). Las subescalas del GMDS de coordinación ojo‐mano (p = 0, 01) y rendimiento (p <0, 01) aumentaron en el grupo de tratamiento, mientras que la puntuación total del grupo de comparación disminuyó, impulsada por el lenguaje (p = 0, 039) y la coordinación ojo‐mano (p = 0, 025) subescalas. Interpretación: Los resultados sugieren que, en los bebés con discapacidad visual, la función visual y ciertos resultados del desarrollo mejoran en respuesta al entrenamiento visual temprano y la adaptación ambiental, y en un contexto interactivo. Treinamento visual e adaptação ambiental precoces para lactentes com deficiência visual: Objetivo: Avaliar a efetividade do treino e adaptação ambiental precoces sobre a função motora e desenvolvimento neurológicos para lactentes com deficiência visual. Método: Este foi um estudo piloto de intervenção clínica. Trinta lactentes (média de idade 5, 9m, DP 2, 1m, variação 4–11m; 16 do sexo masculino, 14 do sexo feminino) com deficiência visual periférica (DVP, n =15) ou deficiência visual cerebral (DVC, n =15) participaram de um programa de intervenção visual de 6 meses. Trinta lactentes pareados (média de idade 6m, DP 1, 4m, variação 4–9m; 18 do sexo masculino, 12 do sexo feminino) serviram como grupo de comparação. As medidas de desfecho primárias foram a acuidade visual, a sensibilidade a contrastes, e funções óculo‐motoras qualitativas. Desfechos secundários foram as pontuações na Escala de Desenvolvimento Mental de Griffiths (EDMG). Resultados: O grupo tratado mostrou melhora significativas em todos os desfechos primários ( p <0, 01). O grupo de comparação melhorou apenas na acuidade visual e sensibilidade a contrastes ( p <0, 01). O grupo tratado mostrou mais melhora na fixação visual ( p =0, 033) e acompanhamento suave ( p <0, 01). O subgrupo DVC mostrou mais melhora na acuidade visual do que o grupo DVP ( p <0, 01). As subescalas de coordenação olho‐mão ( p =0, 01) e desempenho ( p <0, 01)da EGMG aumentaram no grupo tratado, enquanto a pontuação total do grupo de comparação diminuiu, guiadas pelas subescalas de linguagem ( p =0, 039) e coordenação olho‐mão ( p =0, 025). Interpretação: Os resultados sugerem que, em lactentes com deficiência visual, a função visual e certos resultados desenvolvimentais melhoram em reposta ao treinamento visual e adaptações ambientais precoces, e em um contexto interativo.